2017
DOI: 10.1111/jnc.14263
|View full text |Cite
|
Sign up to set email alerts
|

Dense‐core vesicle biogenesis and exocytosis in neurons lacking chromogranins A and B

Abstract: Chromogranin A and B (Cgs) are considered to be master regulators of cargo sorting for the regulated secretory pathway (RSP) and dense-core vesicle (DCV) biogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 46 publications
4
21
0
Order By: Relevance
“…In this report, we show that loss of CgB in the pancreatic islet β-cell has significant effects on glucose-stimulated insulin secretion directly related to its role in granule protein trafficking. Previous studies have demonstrated that loss of CgB negatively impacts hormone release in some endocrine tissues, such as pancreatic islets (Obermüller et al, 2010) and adrenal chromaffin cells (Díaz-Vera et al, 2012;Dominguez et al, 2018), but is dispensable in other cell types including hippocampal neurons (Dominguez et al, 2018). Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this report, we show that loss of CgB in the pancreatic islet β-cell has significant effects on glucose-stimulated insulin secretion directly related to its role in granule protein trafficking. Previous studies have demonstrated that loss of CgB negatively impacts hormone release in some endocrine tissues, such as pancreatic islets (Obermüller et al, 2010) and adrenal chromaffin cells (Díaz-Vera et al, 2012;Dominguez et al, 2018), but is dispensable in other cell types including hippocampal neurons (Dominguez et al, 2018). Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Additionally, granins may chaperone the sorting and/or deposition of secretory cargo, such as prohormones, within the budding granule (Natori and Huttner, 1996), though direct associations with prohormones have yet to be documented. Reduced expression of some granins, such as CgB, has been reported in human T2D islets (Bugliani et al, 2013); however, conflicting knockout studies have hampered clear delineation of its role(s) in granule biology (Díaz-Vera et al, 2012;Hendy et al, 2006;Mahapatra et al, 2005;Dominguez et al, 2018). Global deletion of CgB reduces islet hormone secretion (glucagon, insulin and somatostatin) (Obermüller et al, 2010); however, ultrastructrural analysis failed to reveal defects in granule structure and number, suggesting CgB is not required for dense core granule formation.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the precise role of CgA among all granins expressed in a same secretory cell, the Borges's group generated a double CgA/CgB‐KO mouse line, and observed that the absence of both granins led to giant SG‐like structures with little or no electron dense internal matrix, changes in catecholamine accumulation and in the exocytosis course with a significant reduction of the secretory response in chromaffin cells, indicating an alteration of vesicular catecholamine storage and secretion capacities . Recently, SG biogenesis was investigated in hippocampal neurons from CgA/CgB‐KO mice and surprisingly, no changes were detected in CgA/CgB‐KO neurons which exhibited normal dendritic and axonal length and arborization, synapse density, and synaptic vesicle accumulation, as well as number of secretogranin II (SgII)‐positive SGs and exocytotic events . Thus, the granulogenic activity of CgA, as well as its role in neurosecretion maintenance, appear to be cell‐dependent and despite the biochemical properties shared between CgA and CgB, CgB is unable to restore SG biogenesis in CgA‐deficient PC12 cells (6T3 cells) …”
Section: Chromogranin a Contributes To The Biogenesis Of Secretory Grmentioning
confidence: 99%
“…22,23 Recently, SG biogenesis was investigated in hippocampal neurons from CgA/CgB-KO mice and surprisingly, no changes were detected in CgA/CgB-KO neurons which exhibited normal dendritic and axonal length and arborization, synapse density, and synaptic vesicle accumulation, as well as number of secretogranin II (SgII)-positive SGs and exocytotic events. 24 Thus, the granulogenic activity of CgA, as well as its role in neurosecretion maintenance, appear to be cell-dependent and despite the biochemical properties shared between CgA and CgB, CgB is unable to restore SG biogenesis in CgA-deficient PC12 cells (6T3 cells). 25…”
Section: Chromogranin a Contributes To The Biogenesis Of Secretory mentioning
confidence: 99%
“…Independently from their cargo, LDCVs express a series of integral proteins that, biochemically, make them a relatively homogeneous population of vesicles. Among these are the chromogranins (Bartolomucci et al, 2011 ), which are important regulators of cargo sorting in LDCVs biogenesis, although very recent work in mouse hippocampal neurons has demonstrated that they are not indispensable for LDCVs’ exocytosis (Dominguez et al, 2018 ).…”
Section: State Of Art On High Molecular Weight Neurotransmitter Localmentioning
confidence: 99%